Islamic and Conventional Banking: A Comparison of Financial Performance During the Covid-19 Pandemic - Resfauzi Norma Safarda; Rofiul Wahyudi; Ferry Khusnul Mubarok (Journal of Islamic Economic and Business Research, 2023)
The research aims to compare the financial performance of Islamic banks with conventional banks during the covid-19 pandemic. The sampling method was a purposive sampling technique and obtained 3 Islamic banks and 3 conventional banks. The data analysis technique is descriptive statistical analysis and to answer the proposed hypothesis using the technique of independent sample t-test and Mann Whitney.Â Meanwhile, the CAR, NPF/NPL, and FDR/LDR ratios have no difference. Analysis showed that Islamic banks performed better in Capital Adequacy Ratio and Financing to Deposit Ratio. Conventional banks had a better performance from Return on Asset, Return on Equity, Non-Performing Loan, Operating Costs, and Operating Income.